The UN Food Systems Summit 2021: Lessons of the gender and finance levers - Díaz-Bonilla, Eugenio; McNamara, Brian; Njuki, Jemimah; Swinnen, Johan; Vos, Rob (Agricultural and Applied Economics Association, 2022)
The United Nations Food Systems Summit (UNFSS), held in September of 2021, aimed to move food systems transformation to the top of the global policy agenda. An important element of the UNFSS were “levers of change,” areas of work expected to make a significant positive change within food systems. The UNFSS levers differed in the way they operated, their visibility, their impact on the Summit’s outcome, and the extent to which they feature in post-UNFSS activities and plans. This paper reviews the operation and effectiveness of the levers by discussing and comparing two key levers: gender and finance. The Gender Lever of Change focused on strengthening the role of women in food systems transformation, while the Finance Lever of Change focused on reforming existing financial structures and broadening financial support for optimal food systems. This paper reviews the activities and engagement of these two levers, the main debates. and the process of consultations. It concludes that the levers were instrumental in framing key principles and concrete directions for action to mainstream gender dimensions and to leverage finance for food system transformation. Lacking an agreed outcome document, the UNFSS established a kind of ‘social experiment’ by forming multistakeholder coalitions behind specific areas for food system transformation and by encouraging governments to design, on a voluntary basis, national pathways for such transformations. The outcomes of this social experiment are highly uncertain but could well turn out a way to overcome existing weaknesses in current fragmented mechanisms for food systems governance.